Automotive technology and patent assignee in Malaysia: an exploratory patent - Harun, Aizul Nahar; Maspo, Nur Adib; Md. Issa, Nurhayati; Matsuura, Yoshiyuki; Chuprat, Suriayati; Mohd Mahadzir, Akbariah; Haron, Nuzul Azam; Mohd Nawi, Mohd Nasrun (Semarak Ilmu Publishing, 2023)
The automotive industry in Malaysia has been established for over four decades, following the introduction of the Industrial Master Plan Malaysia (IMP) in 1985, and the subsequent launching of the National Automotive Policy (NAP) aimed at driving the growth of the automotive industry in Malaysia. A key focus of the NAP was industrial research and development to promote the leadership of Malaysian automotive companies in the region. Consequently, the alignment of university-industry research with the NAP is critical in fostering innovation and advancement in automotive technology. This study employs patent analysis to investigate the university-industry research and development of automotive technology in Malaysia. The objective is to identify patent trends in automotive technology developed by university-industry, which can provide crucial insight for researchers and inventors to incorporate the latest patented technology and support future inventions.